Do Stronger Employer Responsibilities Enhance Workplace Accommodation for Sick-Listed Workers? Evidence from a Dutch Reform - Laura Jansen; Viola Angelini; Max Groneck; Raun van Ooijen (Institute of Labor Economics (IZA), 2025)
This paper studies the impact of stronger employer responsibilities for facilitating work resumption of sick or disabled workers on employers' workplace accommodation efforts during sick leave. We exploit a reform in the Netherlands that altered experience rating – i.e., shifting the costs of sick leave and disability insurance to the firm – both for permanent and non-permanent employees. Using unique Dutch survey data on workplace accommodation of long-term sick-listed workers, we show that experience rating has no significant impact on accommodation efforts. Moreover, we provide evidence that the reform led to more firms opting for self-arranging both the sick leave benefits and the reintegration process of sick non-permanent workers, instead of using the public insurance scheme.
Keywords: H32; I13; J14; J24; 330; workplace accommodation; disability insurance; experience rating; employer incentives